Progression From Patterns A to B in Wellens Syndrome - Edwin A. Rodríguez, MD; Anali Salva, MD; José M. Aladio, MD; Diego Costa, MD; Sandra P. Swieszkowski, MD (JACC: Case Reports, 2023)
We describe a clinical case series of 3 patients whose electrocardiogram evolved from type A Wellens syndrome to a type B. We emphasize that the diagnosis and treatment for both patterns is the same and that these findings suggest the evolution of the same disease. (Level of Difficulty: Intermediate.)